Ghana Scaling Week - Ewell, Hanna; Byandaga, Livingstone; Kagabo, Desire; Ouedraogo, Mathieu; Dalaa, Mustapha; Inusah, Sawdiatu Sandra; Yeboah, Stephen; Damba, Tahidu Osman; Sartas, Murat; Girvetz, Evan; Nzuki, Esther (2024)
The AICCRA Ghana Scaling Week workshop, held in Cape Coast Ghana from September 16th to 19th, 2024, focused on advancing the responsible and inclusive scaling of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) solutions to enhance resilience among smallholder farmers in Ghana. The workshop explored diverse scaling approaches and introduced the AICCRA Scaling Framework, focusing on effective demand, technical excellence, and unreliant use of climate-smart solutions. The event was organized over four days, each with a specific focus: Day 1: The diversity of scaling approaches was explored, highlighting the need for impactful, context-specific, and sustainable solutions through well-aligned partnerships. Day 2: The importance of bundling Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) with other services, such as financial inclusion and agricultural inputs, was emphasized to support adaptation and productivity. Day 3: Responsible scaling practices were discussed, focusing on inclusivity, equity, and localized solutions, while Day 4: was dedicated to setting ambitious goals for 2030, such as reaching 5 million farmers and enhancing productivity by 80%. Through responsible and inclusive scaling, AICCRA aims to create lasting impact, improve resilience among smallholder farmers, and promote sustainable agriculture in Ghana. The group set goals to be achieved by the year 2030: • To expand CIS and CSA’s geographical coverage across Ghana, recognizing the need for context-specific climate adaptation and mitigation solutions. • To ensure that five million smallholder farmers have access to CIS-CSA bundles that incorporate knowledge and financial services (crop insurance), physical services, and consumables with 2 million of the beneficiaries being women. • To achieve an 80% increase in farm productivity while creating resilient communities that are food secure and prosperous. • To ensure that women have access to “smart” seeds and essential resources for effective and efficient crop production.